2007
DOI: 10.1200/jco.2006.07.5754
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Chemotherapy-Naïve Patients ≥ 70 Years of Age Treated With Erlotinib for Advanced Non–Small-Cell Lung Cancer

Abstract: Purpose This is a phase II, multicenter, open-label study of chemotherapy-naïve patients with non–small-cell lung cancer (NSCLC) and age ≥ 70 years who were treated with erlotinib and evaluated to determine the median, 1-year, and 2-year survival. The secondary end points include radiographic response rate, time to progression (TTP), toxicity, and symptom improvement. Patients and Methods Eligible patients with NSCLC were treated with erlotinib 150 mg/d until disease progression or significant toxicity. Tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(172 citation statements)
references
References 33 publications
3
163
3
3
Order By: Relevance
“…However, since the occurrence of skin rash is associated with the response rates and survival duration [1,41], discontinuance of the drug is unbeneficial for the treatment of cancers. Thus, role of dermatologists is important to control skin rash tolerated, as long as the rash does not reach grade 3 (severe or medically significant but not immediately lifethreatening; hospitalization or prolongation of hospitalization indicated; disabling; limiting self care ADL).…”
Section: Resultsmentioning
confidence: 99%
“…However, since the occurrence of skin rash is associated with the response rates and survival duration [1,41], discontinuance of the drug is unbeneficial for the treatment of cancers. Thus, role of dermatologists is important to control skin rash tolerated, as long as the rash does not reach grade 3 (severe or medically significant but not immediately lifethreatening; hospitalization or prolongation of hospitalization indicated; disabling; limiting self care ADL).…”
Section: Resultsmentioning
confidence: 99%
“…reported that a 73-year-old male squamous cell carcinoma patient with the exon 21 L858R received erlotinib and showed SD. (39) The patient's PFS from the initiation of erlotinib was 3.4 months. Rosell et al reported 19 large-cell carcinoma patients harboring exon 19 deletions or exon 21 L858R EGFR mutations received erlotinib, and the hazard ratio of the PFS was 1.15 in comparison with 176 adenocarcinoma patients harboring the exon 19 deletion or exon 21 L858R EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase 2 trial of erlotinib, an inhibitor of the epidermal growth factor receptor for elderly patients, demonstrated robust median survival for front-line therapy of advanced NSCLC. 17 Thus, individualized treatment approaches with existing agents, and continued evaluation of other novel agents, remain major goals for improving outcomes in elderly NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%